2019
DOI: 10.1002/cam4.2013
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone inhibits IKKβ kinase activity to interrupt the NF‐κB/COX‐2‐mediated signaling cascade and induces apoptosis regulated by the mitochondrial translocation of cofilin in glioblastoma

Abstract: Isoalantolactone (IATL), a sesquiterpene lactone compound, possesses many pharmacological and biological activities, but its role in glioblastoma (GBM) treatment is still unknown. The aim of the current study was to investigate the antiglioma effects of IATL and to explore the underlying molecular mechanisms. In the current study, the biological functions of IATL were examined by MTT, cell migration, colony formation, and cell apoptosis assays. Confocal immunofluorescence techniques, chromatin immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This suggested that alterations in the location of cofilin-1 rather than its expression level were the primary cause of As 2 o 3 -induced apoptosis in NB4-R1 cells, which was consistent with the aforementioned studies (35)(36)(37). Besides, Xing et al (38) demonstrated that isoalantolactone inhibits IKKβ kinase activity and promotes apoptosis of glioblastoma cells by inducing translocation of cofilin-1 to the mitochondria and the release of mitochondrial cytochrome C to the cytoplasm, which activates caspase-3/9. In human leukemia cells, cofilin-1 translocation to the mitochondria could induce mitochondrial injury and cell apoptosis (39).…”
Section: Discussionsupporting
confidence: 82%
“…This suggested that alterations in the location of cofilin-1 rather than its expression level were the primary cause of As 2 o 3 -induced apoptosis in NB4-R1 cells, which was consistent with the aforementioned studies (35)(36)(37). Besides, Xing et al (38) demonstrated that isoalantolactone inhibits IKKβ kinase activity and promotes apoptosis of glioblastoma cells by inducing translocation of cofilin-1 to the mitochondria and the release of mitochondrial cytochrome C to the cytoplasm, which activates caspase-3/9. In human leukemia cells, cofilin-1 translocation to the mitochondria could induce mitochondrial injury and cell apoptosis (39).…”
Section: Discussionsupporting
confidence: 82%
“…Mitochondrial translocation of cofilin induced by cyclohexene was found to be the underlying mechanism of anti-leukemia ( 37 ). Cofilin was confirmed to translocate to the mitochondria after isoalantolactone-induced apoptosis in GBM ( 38 ). These results indicated that mitochondrial translocation of cofilin is pivotal for inducing cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…They are often used either as drug leads or as actual drugs. Isoalantolactone (IATL) is a sesquiterpene lactone naturally occurring in the roots of Inula helenium L. IATL has been reported to exert cytotoxic effects against a variety of cancer cells, including pancreatic cancer ( Zhang et al, 2021 ), esophageal cancer ( Lu et al, 2018 ; Wen et al, 2018 ), hepatocellular carcinoma ( Kim et al, 2021 ), prostate cancer ( Rasul et al, 2013 ; Chen et al, 2018 ; Huang et al, 2021 ) and glioblastoma ( Xing et al, 2019 ). The anticancer effects of IATL mainly involve the induction of apoptosis, cell cycle arrest and autophagy ( Weng et al, 2016 ; Chen et al, 2018 ; Lu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%